SOSIALISASI DESAIN FORMULIR STATUS KESEHATAN LANSIA - Nurul Faidah; I Made Sudarma Adiputra; Ni putu Wiwik Oktaviani; Ni Kadek Muliawati; Ni Luh Gede Puspita Yanti (Bajang Institute, 2022)
In the Elderly Posyandu activities, health checks are carried out by health workers at the East Denpasar Regional Health Center but there is no medical record form that can be used to document the results of the health examination. During the posyandu activities for the elderly, the cadres checked blood pressure, height, weight, glucose levels, and cholesterol. Therefore, we carried out community service by socializing the elderly assessment form and how to enter these data into the design of the form. The purpose of community service is to improve the ability of posyandu cadres in understanding and documenting the elderly health status form. The method carried out was conducting a pre-test which contained knowledge of cadres related to the assessment of the elderly, then socialization, demonstration and assistance were carried out in filling out the elderly health status form. The target is the elderly posyandu cadres of Banjar Tunjung Sari. The assistance provided includes how to fill out medical record forms for the assisted elderly, what items must be filled out, and how to manage the forms. After doing community service, the results of the knowledge before being given socialization obtained 4 (80%) lack of knowledge, after being given socialization and knowledge assistance 3 (60%) knowledge was good and cadres were able to fill out health forms and document the elderly health status forms. Health status can be continuously documented